Pengaruh Perbandingan Tepung Pisang (Musa paradisiaca L.) dan Tepung Kacang Merah (Phaseolus vulgaris L.) Terhadap Karakteristik Brownies Kukus - Malissa, Tri Ayu; Ekawati, I Gusti Ayu; Yusasrini, Ni Luh Ari (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 3 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i03.p21, 2023)
This research was to determine the effect comparison of banana flour and red bean flour on the charateristics of steam brownies and to determine the best ratio of banana flour and red bean flour to produce steam brownies with the best characteristics. The experimental design used in this study was a Completely Randomized Design (CRD) with the comparison treatment of banana flour and red bean flour which consists of 6 levels ratio: 100%:0%, 96%:4%, 92%:8%, 88%:12%, 84%:16%, and 80%:20%. The treatment was repeated 3 times to obtain 18 experimental units. The data obtained were then analyzed by the Analysis of Variance (ANOVA) and if the treatment had a significant effect on the observed parameter, it would be continued with the Duncan’s Multiple Range Test (DMRT). The results showed that the comparison of banana flour and red bean flour had a significant effect on water content, ash content, protein content, fat content, carbohydrate content, crude fiber content, hedonic test on color, aroma, texture, taste, and overall acceptance and scoring test such as texture and taste. The comparison of 84% banana flour and 16% red bean flour had the best characteristic of steam brownies with the criteria of water content 34.72%, ash content 2.90%, fat content 34.21%, protein content 8.40%, carbohydrate content 19.83%, crude fiber content 5.96%, color was liked, aroma was liked, soft texture was liked, banana taste was liked, and overall acceptance was liked.